New record of Chromistan parasites of copepods and rotifers in Iraqi marine and brackish waters - Khalaf, T.A.; Awad, A.H.H.; Morad, M.S.S. (Mesopotamian Journal of Marine Sciences, 2022)
The present study was focused on the infections of some zooplankton groups (copepoda and rotifer) with ecto and endo parasites in Iraqi marine and estuarine brackish water during the period from January to the end of October 2010 by seasonally intervals. Samples were collected from 5 selected stations represent Iraqi marine and brackish waters. Many parasites were recorded on copepods and other zooplankton in the study area, these are: Ellobiopsis chattoni, Ellobiopsis sp., Thalassomyces sp., Blastodinium sp., Zoothamnium sp., Dinoflagellate and peritrich ciliates. These parasites were recorded for the first time in Iraqi marine and brackish waters except for Ellobiopsis chattoni, and the genus Thalassomyces sp. which were recorded in Kuwaiti waters before. The percentage and the intensity of infections were studied; the highest percentage of infections copepods was 35.7% in winter at station 4, while the lowest was 0.73% at stations 2 during autumn. The highest percentage of infections in rotifers was 9.49% at station 1 during autumn, while the lowest percentage was 0.15 % at station 3 during winter. The highest mean intensity of the copepods was 12.03 at station 1 during summer, while the lowest value was 1.05 in the same station during autumn. The highest mean intensity of the copepods and rotifers was 6.3 at station 2 during summer, while the lowest was 0.8 in the same station during autumn. Scanning Electron Microscope (SEM) was used in this study for identification of some ecto parasites of copepods.